Probing the responses of four chicory ecotypes by ethylene accumulation and growth characteristics under drought stress - Sadeghi, Hossein; Ghanaatiyan, Kimiya (Italian Journal of Agronomy, 2017)
Water deficit is the largest limiting abiotic factor in agriculture and will increase in future. Evaluating the drought stress-induced changes in growth parameters as well as the leaves ethylene accumulation of medicinal plants to grow these in arid and semi-arid areas has particular importance. Chicory (Cichorium intybus L.) is a famous medicinal herbal plant which grows in most parts of Iran. A factorial greenhouse experiment was conducted to evaluate the effect of drought stress [100 (as a control), 80, 60 and 40% of field capacity (FC)] on morphophysiological parameters as well as the leaves ethylene accumulation of four chicory ecotypes. The results showed a significant effect of drought on plant height, leaf area, shoot moisture content and total dry matter production of chicory ecotypes which were reduced under drought stress. Under increasing drought level the Siyah Shiraz (Kh) ecotype performed better by maintaining more growth characters, thereby leading to more production of dry matter than the other ecotypes. Isfahan ecotype was the most affected by rising tensions and showed more reduction in growth traits. Drought stress also considerably changed leaf ethylene content, that made the leaf ethylene biosynthesis to be significantly higher under severe (60 and 40% FC) stress when compared to control (100% FC) and was significantly higher in drought-tolerant chicory ecotype (Kh). In general, it can be concluded that (Kh) was superior to other ecotypes in terms of growth and leaves ethylene accumulation, and can be suitable for cultivation in arid regions.